OFW: Migration and development - Florian A. Alburo (University of the Philippines, School of Economics (UPSE), 2024)
This paper attempts to review the Overseas Filipino Worker (OFW) phenomenon through selected aspects of it - past and present trends, structural issues, and development context. While the OFW system appears to be beneficial to the county, it is overrated. It is unclear what policies were really set in place to eventually phase it out. While it alleviates poverty, whether poverty reduction is permanent is also unclear. Structurally, the OFW profile shows a "cream of the crop" relative to the labor force and tend to deploy more females creating problems with those left behind. The development context compares the experience of the Philippines with other countries which were able to turnaround from being net sources of migrant workers to net absorbers. Three development policies are explored to partly explain the divergence between migrant worker movement in the Philippines and others.
Keywords: F1; F2; J3; J6; O4; 330; Overseas Filipino Worker; OFW; Migration and Development